2017
DOI: 10.3390/fluids3010001
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Convection in the Presence of a Precipitation Reaction in a Porous Medium: A Comparison of Linear Stability and Numerical Approaches

Abstract: Abstract:Reactive convection in a porous medium has received recent interest in the context of the geological storage of carbon dioxide in saline formations. We study theoretically and numerically the gravitational instability of a diffusive boundary layer in the presence of a first-order precipitation reaction. We compare the predictions from normal mode, linear stability analysis, and nonlinear numerical simulations, and discuss the relative deviations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…While simple reactions consuming A out of the solution stabilize convection (Ghesmat et al (2011), Andres & Cardoso (2011, Cardoso & Andres (2014), Ward et al 2014, Kim & Choi (2014), Kim & Kim (2015), Ghoshal et al (2018)), various theoretical works have shown that A+B→C reactions can accelerate or decelerate the convective dynamics with respect to the nonreactive case and that the steady-state dissolution flux of species A varies with the difference ∆RCB (Loodts et al (2014(Loodts et al ( , 2015(Loodts et al ( , 2017(Loodts et al ( , 2018, Jotkar et al (2019), Ghoshal et al (2017).) For equal diffusion coefficients, if ∆RCB > 0, the density profiles are monotonic.…”
Section: Influence Of a + B → C Reactions On Convective Dissolutionmentioning
confidence: 99%
“…While simple reactions consuming A out of the solution stabilize convection (Ghesmat et al (2011), Andres & Cardoso (2011, Cardoso & Andres (2014), Ward et al 2014, Kim & Choi (2014), Kim & Kim (2015), Ghoshal et al (2018)), various theoretical works have shown that A+B→C reactions can accelerate or decelerate the convective dynamics with respect to the nonreactive case and that the steady-state dissolution flux of species A varies with the difference ∆RCB (Loodts et al (2014(Loodts et al ( , 2015(Loodts et al ( , 2017(Loodts et al ( , 2018, Jotkar et al (2019), Ghoshal et al (2017).) For equal diffusion coefficients, if ∆RCB > 0, the density profiles are monotonic.…”
Section: Influence Of a + B → C Reactions On Convective Dissolutionmentioning
confidence: 99%
“…By the Oberbeck–Boussinesq approximation, density changes in the system have been neglected except for the buoyancy term Δ ρgh . 77–86…”
Section: Resultsmentioning
confidence: 99%